The Clinical Utility of Circulating Epstein-Barr Virus DNA Concentrations in NK/T-Cell Lymphoma: A Meta-Analysis - Liu, Ze-Long (Dis Markers, 2018)
BACKGROUND: Circulating Epstein-Barr virus (EBV) DNA concentrations were reported to have prognostic value for NK/T-cell lymphoma patients in limited small-scale studies. In this study, we aimed to evaluate the clinical utility of circulating EBV-DNA concentrations to a large sample of NK/T-cell lymphoma patients. METHODS: We conducted this meta-analysis, which included a total of 15 prospective and retrospective comparable studies to assess the association between pretreatment EBV-DNA (pre-DNA), posttreatment EBV-DNA (post-DNA), and clinical outcomes of NK/T-cell lymphoma patients. We chose overall survival (OS) as the primary endpoint and progression-free survival (PFS), complete response (CR), and overall response rate (ORR) as secondary endpoints. RESULTS: High pre-DNA and detectable post-DNA were both significantly correlated with poorer OS in NK/T-cell lymphoma patients (P < 0.05), with hazard radios (HRs) equal to 3.45 and 2.30, respectively. High pre-DNA and detectable post-DNA also predicted poorer PFS. Additionally, high pre-DNA was found to be significantly correlated with both worse CR and ORR, which indicated worse treatment response. CONCLUSION: Circulating EBV-DNA concentrations provides prognostic values of survival and treatment response in NK/T-cell lymphoma patients.